The Beneish M-Score Model in Detecting Fraudulent Financial Reporting: The Hexagon Perspective Theory - Kusuma, Sherawanti Permata; Oktafiyani, Melati; Pamungkas, Imang Dapit; Ratnawati, Juli (Jurnal Penelitian Ekonomi dan Bisnis, 2024)
This research aims to investigate the effect of fraud on fraudulent financial reports (FFR) using the hexagon theory. The seven factors were financial stability, external pressure, ineffective monitoring, auditor changes, director changes, arrogance, and collusion. This study has a population of health companies listed on the IDX in 2018-2021. This study uses a quantitative approach. Based on the logistic regression analysis, the study finds that financial stability, change director, and arrogance affect FFR. On the other hand, external pressure, ineffective monitoring, auditor change, and collusion do not affect FFR. Keywords:Fraudulent financial reporting, Hexagon theory, Beneish M-Score